Between fixities and flows: Navigating place attachments in an increasingly mobile world. (February 2019) - Di Masso, Andrés; Williams, Daniel R.; Raymond, Christopher M.; Buchecker, Matthias; Degenhardt, Barbara; Devine-Wright, Patrick; Hertzog, Alice; Lewicka, Maria; Manzo, Lynne; Shahrad, Azadeh; Stedman, Richard; Verbrugge, Laura; et al.
Abstract: This paper develops a theoretical argument for how place attachments are forged and become dynamically linked to increasingly common mobility practices. First, we argue that mobilities, rather than negating the importance of place, shift our understanding of place and the habitual ways we relate to and bond with places as distinct from a conception of place attachment premised on fixity and stability. Second, we document how the body of research on place attachment has both reinforced and contested 'sedentaristic' assumptions criticized within the so-called 'mobilities turn' in the social sciences. Third, we present a conceptual framework, built around different modes of interrelation between fixity and flow, as a way to re-theorize, link and balance the various studies of place attachment that have grappled with mobility. Finally, we sketch out the main research implications of this framework for advancing our understanding of place attachment in a mobile world. Highlights: Mobility complicates sedentaristic assumptions in place attachment research. Aspects of fixity and flow shape place attachments related to mobility. The fixity-flow framework emphasizes place attachments as dynamic and fluid. The fixity-flow framework reconceptualizes mobility-related place attachment research.